Bacteriocin-producing Pediococcus acidilactici BAMA 15 isolated from "naniura" traditional foods in North Sumatra, Indonesia - SUBANG AINI NASUTION; EDY FACHRIAL; CHRISMIS NOVALINDA GINTING; LIENA LIENA; FINNA PISKA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nasution SA, Fachrial E, Ginting CN, Liena, Piska F. 2023. Bacteriocin-producing Pediococcus acidilactici BAMA 15 isolated from "naniura" traditional foods in North Sumatra, Indonesia. Biodiversitas 24: 2830-2835. Lactic Acid Bacteria (LAB) have beneficial properties for their hosts, potentially promoting health and balancing the normal gut flora. Meanwhile, bacteriocin is a bacteriostatic polypeptide used as a food preservative. LAB are generally produced from fermented products, such as dengke naniura, a typical Toba Batak food. Therefore, it is estimated that the LAB present in this food has the potential as a probiotic and produces bacteriocin, an antimicrobial polypeptide compound. The purpose of this study was to identify the LAB species found in dengke naniura and to characterize the bacteriocin generated by them. The first study stages included the isolation and biochemical and morphological characterization of LAB. Nine LAB isolates (BAMA 10-11, BAMA 15-20, and BAMA 25) were isolated from the samples. The best strain for use as a probiotic was Pediococcus acidilactici BAMA 15 because its antimicrobial activity against E. coli and S. aureus was 6.44 and 7.53 mm, respectively. The bacteriocin produced has a molecular weight estimated to be ?12 kDa.